New materialism: An end to certainty - Marn, Travis; Cleave, Jessica Van (Theory and Philosophy in Qualitative Research Methods: Key Concepts, 2026)
The purpose of this entry is to provide an orientation to new materialism, a form of inquiry or philosophy that brings renewed interest to materiality. New materialist philosophies offer an end to certainty, an end to the belief that meaning, knowledge, and agency are fixed and stable. New materialism, however, is not a cohesive body of work but rather a collection of theories, theorists, works, and assumptions, each with its own goals, methods, and desired end points. What constitutes new materialism, what contributes to new materialism, and what inspires new materialist scholarship are not necessarily the same. We trace some of the historical influences of new materialism, highlighting key theories and theorists, describing the intersecting philosophical traditions that mutually constitute new materialism, and exploring the implications of new materialism both for social justice and for qualitative research. © 2026 selection and editorial matter, Aaron M. Kuntz; individual chapters, the contributors.
Keywords: dept.cur

A phenomenological study of the racial sensemaking of Chinese international doctoral students in the United States during and post the COVID-19 pandemic - Wang, Peiwen (International Journal of Qualitative Studies in Education, 2025)
Keywords: China; Ethnography; Interpretative phenomenological analysis; Pandemic; Phenomenology (philosophy); Qualitative research; Racism; Semi-structured interview; Sensemaking; dept.cur

Disconnected in a connected world: improving digital literacies instruction to reconnect with each other, ideas, and texts - Marangell, Joseph; Randall, Régine (Education Sciences, 2025)
This commentary addresses a problem of practice related to student disengagement in technology-rich classrooms, where learners are digitally connected but socially and academically disconnected. Although not an empirical study, the commentary draws on instructional examples from secondary- and graduate-level teaching. The authors examine how digital literacy instruction can strengthen engagement, reading comprehension, and ethical participation in online environments. The article highlights strategies such as the workshop model, multimodal composition, digital content curation, and the use of mentor texts to support critical thinking and collaborative learning. These practices aim to develop students’ analytical skills, awareness of audience, and recognition of their own positionality in digital spaces. Across courses, the authors reflected on increased student engagement when digital tools were used not simply for task completion but to support inquiry, discourse, and authentic creation for real audiences.
Keywords: Comprehension; Computer science; Critical thinking; Digital literacy; Disengagement theory; Linguistics; Literacy; Mathematics education; Pedagogy; Psychology; Reading (process); Reading comprehension; Sociology; Student engagement; Task (project management); dept.cur

“I’m like white people here”: Chinese international doctoral students’ perception of ethno-racial issues in China (poster 23) - Wang, Peiwen (AERA 2025 Annual Conference, 2025)
Keywords: China; Law; Media studies; Perception; Political science; Psychology; Sociology; White (mutation); dept.cur

The failures and possibilities of philosophy in the material world - Van Cleave, Jessica; Marn, Travis; Wolgemuth, Jennifer (International Review of Qualitative Research, 2025)
Keywords: Engineering; Engineering ethics; Epistemology; Philosophy; dept.cur

Manufacturing Trustworthiness in Qualitative Research as a Writerly and Readerly Accomplishment: Introduction to the Special Issue - Van Cleave, Jessica; Wolgemuth, Jennifer; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Construct (python library); Product (mathematics); Qualitative research; Space (punctuation); Theme (computing); Tinker; Trustworthiness; dept.cur; possibility; publication; scholarly writing; trustworthiness

Producing Participants: Trustworthiness as Convenient Fiction - Van Cleave, Jessica; Marn, Travis (Qualitative Inquiry, 2025)
Keywords: Objectivity (philosophy); Qualitative research; Quality (philosophy); Reputation; Rigour; Transparency (behavior); Trustworthiness; Verisimilitude; dept.cur; fiction; methodologies; qualitative criteria; qualitative research; transparency; trustworthiness

#scholar #famous #monster - Wolgemuth, Jennifer; Lester, Jessica; Guyotte, Kelly; Koro‐Ljungberg, Mirka; Marn, Travis (Educational Researcher, 2025)
Academic success is now coupled with social media engagement. Social media has become so normalized in the academy that absent a carefully curated social media presence, scholars risk being seen as unscholarly, unproductive, and unpopular. This article lays bare the pressures, mechanisms, and monstrosities of using social media to promote scholarship. We argue that the widespread adoption of social media outpaces critical attention to its ethics and wonder about the future of public scholarship and the monstrous scholarly selves we are becoming. Thinking of monstrosity, with Krecˇicˇ and Žižek, as the preontological domain that rests beneath society and constitutes alterity and otherness, we ask what kinds of #scholarfamousmonsters we want to be, become, and promote in the digital era.
Keywords: Aesthetics; Art; Epistemology; Law; Literature; Media studies; Monster; Philosophy; Political science; Psychology; Scholarship; Social media; Social psychology; Sociology; Wonder; dept.cur; peer-reviewed

Elementary preservice teachers' use of the crosscutting concepts to plan NGSS ‐aligned science lessons in explicit versus non‐explicit contexts - Sherwood, Carrie‐Anne; Benedict‐Chambers, Amanda (School Science and Mathematics, 2025)
Keywords: Context (archaeology); Discipline; Lesson plan; Mathematics; Mathematics education; Next Generation Science Standards; Pedagogy; Plan (archaeology); Psychology; Science education; Significant difference; Sociology; dept.cur; peer-reviewed

Academic bullying as a racialized phenomenon in STEM higher education: Centering the experiences of Asian international doctoral students - Wang, Peiwen (Journal of International Students, 2024)
While students of color’s experiences of academic bullying from their advisors have been documented in the literature (e.g., Moss & Mahmoudi, 2021), little is known regarding the role that race plays in the normalization and perpetuation of academic bullying within higher education. Utilizing Asian critical theory (AsianCrit) as both the theoretical and analytical lens, this phenomenological study centers five STEM Asian international doctoral students’ experiences of academic bullying through semi-structured interviews. It is found that racialized academic bullying is operationalized by a) legitimizing exploitation through racializing discourses; b) maintaining White supremacy across transnational contexts; and c) intersecting systems of oppression. Implications and recommendations are offered as to what stakeholders can do collectively to address racialized academic bullying towards minoritized students and to combat systemic inequities and oppression.
Keywords: STEM; dept.cur; peer-reviewed

Planning for Equitable Student Sensemaking: An Examination of Preservice Teachers Noticing of Elementary Science Lesson Plans - Benedict-Chambers, A.; Sherwood, C.-A. (Journal of Science Teacher Education, 2024)
Designing and analyzing lesson plans is a ubiquitous practice in teacher education, and yet we know little about how preservice teachers (PSTs) notice elements of their lesson plans that afford opportunities for supporting equitable student sensemaking. We investigate how the use of a tool, a framework for supporting equitable sensemaking, guided 36 PSTs to notice four features of equitable sensemaking in their plans. Qualitative analysis of PSTs’ comments about their plans generated a coding rubric and three associated levels for noticing. These levels included (1) paying little to no attention to explicit strategies and making assumptions about the ways that traditional classroom practices might facilitate equitable sensemaking; (2) attending to some strategies but providing few details; and (3) attending to and making connections between specific moves and broader principles and practices of supporting equitable student sensemaking. Guided by the tool, PSTs were able to provide elaborate details about their plans to design instruction to engage students in authentic scientific work focused on investigating and explaining phenomenon (feature 4) and to position students as knowers (feature 2), but they struggled to discuss explicit ways to leverage students’ lived experiences in their science lessons (feature 3) and facilitate equitable engagement and participation (feature 1). This suggests that even with the use of a tool, it may be challenging for PSTs to attend to and describe in detail strategies for leveraging students’ out-of-school lives and interests for science learning and explicit classroom strategies for making learning accessible and engaging for all. © 2024 Association for Science Teacher Education.
Keywords: Equitable science instruction; dept.cur; methods courses; noticing; peer-reviewed; preservice teachers

Proverb: Nearly Spring in a New Hampshire Barn - Randall, Regine (On and Off the Road: Poems of New Hampshire, 2020)
"This poetry anthology, with poems from poets throughout New England and from other states - is a result of Peterborough Poetry Project's second poetry contest. We invited poets, writers, and observers to submit up to three poems about New Hampshire - past, present, future, or fantasy. Forty-eight poems from the contest form this book. The poems are in three different sections by themes: People, Places, and The Wild, but readers may find that several poems have more than one theme. A poem may appear to be about nature, but also our reactions to it. Another poem may appear to be true, but might be pure fantasy. Such is the nature of poetry: read it for the obvious, then read it again to see if more reveals itself"--Back cover
Keywords: dept.cur; literary-poetry

New Literacies of Online Research and Comprehension - Leu, Donald J.; Kiili, Carita; Forzani, Elena; Zawilinski, Lisa; O'Byrne, W. Ian; McVerry, J. Greg (The Encyclopedia of Applied Linguistics, 2021)
This entry explores the question of how to conceptualize literacy as a deictic concept, one that continually changes as new technologies for literacy and learning emerge. It suggests a dual-level conceptualization of theory: a New Literacies theory as an overarching theory that encompasses perspectives and findings from the many studies of literacy, which are referred to as new literacies theories, using lower case. It then focuses special attention on an important lower-case theory, the new literacies of online research and comprehension. This new literacies theory frames online reading as a process of problem-based inquiry involving the new skills, strategies, dispositions, and social practices that take place as we use the Internet to solve problems and answer questions. Current understanding of online reading to learn from a New Literacies perspective is informed by recent research using assessments that measure students' ability to conduct online research in science and comprehend what they read in a virtual online world. Findings suggest that online reading requires different skills than reading paper materials; that differences across modes of reading are important for school learning; and that the Internet is best conceived as a literacy issue rather than a technology issue.
Keywords: Literacy; Literacy Practices Online; New Literacies; Online Reading; Teaching Reading; dept.cur

Extending Student (R)esponse to (E)ngagement in a Bilingual Classroom: An Analysis of Identity-Infused Classroom Discourse - Ferraro, Marisa (Empowering Students Through Multilingual and Content Discourse, 2023)
The growing diversity of students in schools has raised important questions regarding how students learning English and discipline-content simultaneously succeed academically. This challenge has been exacerbated by disparities in resources among multilingual communities throughout the COVID-19 pande...
Keywords: dept.cur

Cultivating Language and Identity through Multimodal Literacies: Back to the StoryBoard - Ferraro, Marisa; Mendoza, Kristin Bengtson (Multimodal Literacies in Young Emergent Bilinguals: Beyond Print-Centric Practices, 2022)
Keywords: dept.cur

Axes of support: Explicit to implicit and practical to epistemic - Fick, S.J.; Arias, A.M.; Vo, T.; Sherwood, C.-A.; Benedict-Chambers, A.; Lo, A.S. (International Society of the Learning Sciences (ISLS), 2020)
Drawing from analyses of teaching and learning, we posit a theoretical framework of axes, practical to epistemic and explicit to implicit, which frame four quadrants of support needed to know how and why to use the crosscutting concepts in sensemaking. This work has implications for the design of learning environments that use the crosscutting concepts in scientific sensemaking. © ISLS.
Keywords: Computer aided instruction; Four quadrant; Learning environments; Sensemaking; Teaching and learning; Technology transfer; Theoretical framework; dept.cur

Applied qualitative data analysis after the ontological turn - Marn, T.M.; Wolgemuth, J.R. (Qualitative Report, 2021)
In this article we demonstrate the use and usefulness of new materialism as an analytic lens in applied qualitative inquiry. Intended as a possible entry point to applied inquiry after the ontological turn, we draw on Barad's agential realism to analyze three existing transcripts of focus groups conducted with healthcare workers, traditional birth attendants, and mothers to explore the postnatal care referral behavior of traditional birth attendants in Nigeria. We describe elements of our data analysis process including deep reading, summoning of the inquiry, delaying the inquiry, attuning to glowing data, and writing. We explore how the research phenomenon enacted agential cuts that distinguished participants (healthcare workers, traditional birth attendants, and mothers) and relayed their participation in the focus group. We show how the inclusion of the mothers' babies and the transcripts themselves made available some understandings at the possible exclusion of others. Our Baradian, new materialist analysis shows the inextricability of interview materials (things) and language (discourse) and demonstrates that all applied research is bounded and affected by its material conditions. As a point of entry, we hope our illustration sensitizes applied qualitative researchers to how research decisions, research materials, and research cultures produce what can be known and lived within and beyond the research encounter. © 2021 Nova Southeastern University. All rights reserved.
Keywords: dept.cur; peer-reviewed

From Leaders to Accomplices: Autoethnography as Praxis in Teacher Education - Powell, Jessica (Re-Imagining Transformative Leadership in Teacher Education, 2021)
This is the third and final book in the series Transformative Pedagogies in Teacher Education. Like the first two books in the series it is geared towards practitioners in the field of teacher education. This third book focuses on transformative leadership in teacher education. In other words, the kind of leadership and practices that will be important and necessary to bring about the kind of changes that both teachers and students seek to improve educational outcomes for all students, but in particular Black, Indigenous and racialized students who have been traditionally underserved by the education system. Teacher leadership plays an important role in transformative educational change that challenges all forms of oppression and white supremacy. This book features chapters by a collection of scholars, teacher educators, researchers, teacher advocates and practitioners drawing on their research and experiences to explore critical issues in teacher education. The book will be useful to teacher educators working with teacher candidates in different contexts, experienced teachers and school leaders. Given demographic shifts and the need for educators to respond to growing diversity in schools, educators will find valuable strategies in Transformative Pedagogies in Teacher Education: Re-Imagining Transformative Leadership in Teacher Education they can employ in their own practice. In addition to valuable strategies, authors explore different approaches and perspectives critical in these changing and challenging times. Critical notions of education are posited from different perspectives and contexts. This book will be useful for teacher education programs, principal preparation programs, in-service teachers, school boards and districts engaging in ongoing professional development of teachers and school leaders.
Keywords: Education / Leadership; Education / Professional Development; Education / Teaching Methods & Materials / Social Science; dept.cur

On the sidelines of what works: scientifically based indifference - Wolgemuth, Jennifer R.; Marn, Travis M.; Sabnis, Sujay (International Journal of Research & Method in Education, 2021)
A team of systematic reviewers successfully completed a government-commissioned review of ‘what works to improve post-school outcomes for youth with disabilities’ in 2012. Despite its success, interviews with 10 review team members revealed dissatisfaction with the process and indifference to its outcomes. The purpose of our analysis was to examine how the systematic review process itself led to review team members’ feelings of indifference, resignation, and pessimism. Drawing on the writings of Henry Giroux, Gert Biesta, and Hanna Arendt that warn of the death of democracy and the rise of totalitarianism, we explored how the systematic review certification process, examinations, rules, and structures deadened democratic deliberation and critique necessary, we argue, to conducting good educational science. We end with a call for systematic reviews in education whose researchers, products, and processes remain ethically oriented to keeping democracy alive. © 2021 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: dept.cur; peer-reviewed

Becoming allies accomplices: Problematizing the intersection of reflection and action through pre-service teachers’ autoethnographies as praxis - Sinclair, Meredith N; Powell, Jessica S (International Journal of Critical Pedagogy, 2020)
This paper explores the phenomenon of pre-service teachers becoming accomplices for racial justice. Using hermeneutic phenomenology, we examine the experiences of three white, female pre-service teachers navigating this terrain. A framework we are naming autoethnography as praxis emerged from this inquiry. Our research interrogates the notion of white allies and the intersection of critical dialogue and action in pre-service teacher education. Building off of perspectives in critical race and critical whiteness studies, this work is grounded in the reality of the material permanence of white supremacy that white teachers must acknowledge and develop tools to dismantle. Autoethnography as praxis moves students from simply analyzing and reporting their experiences (including their emerging understanding of white privilege) through autoethnography to examining how their experiences have shaped and will continue to shape their identities and practices as teachers. By reframing autoethnography as a dialogue between researcher and her texts, we hope to push beyond reflection to action. By engaging participants in reflection on their actions, autoethnography as praxis also addresses the flaw of white teachers acting as benevolent allies who set their own agenda and position people of color as “needing their assistance.” © 2020, University of North Carolina at Greensboro. All rights reserved.
Keywords: Anti-racist pedagogy; Praxis; Social justice; Teacher education; Whiteness; dept.cur; dept.eng; peer-reviewed; ⛔ No DOI found

Responding to Heteronormativity: Lesbian, Gay, Bisexual and Asexual Preservice Teachers’ Dreams and Fears - Bower-Phipps, Laura (Current Issues in Education, 2020)
Heteronormativity, the “privileging of heterosexuality through its normalization” (Jackson, 2006, p. 109), causes confusion and anxiety for many lesbian, gay, bisexual, and asexual preservice teachers as they consider how they will talk about their lives with students. This article explores how preservice teachers have experienced the normalization of heterosexuality and the ways in which these experiences will shape their professional practices. Focus group and follow up interviews with lesbian, gay, bisexual, and asexual preservice teachers were analyzed using a constant comparison method. Findings suggest that participants’ professional vision was largely a response to heteronormativity. They wanted to be out, be role models, and create safe spaces; yet they felt unable to achieve this vision in what they perceived as heteronormative school climates. Implications for teacher preparation programs and policies include the importance of equipping all preservice teachers to identify and disrupt heteronormativity in schools.
Keywords: dept.cur; peer-reviewed; ⛔ No DOI found

“The Goals Remain Elusive”: Using Drawings to Examine Shifts in Teachers’ Mental Models Before and After an NGSS Professional Learning Experience - Sherwood, Carrie-Anne (Journal of Science Teacher Education, 2020)
Teachers’ ability to effectively enact the ambitious vision of the NGSS depends on their understanding of the conceptual and instructional shifts required, and their interpretation of how to implement these shifts in their classrooms. Thus, understanding teachers’ practical knowledge regarding the shifts is an important step in supporting them to effectively implement the NGSS vision. This study used a mental models framework and teacher drawings to examine the practical knowledge of 22 in-service secondary science teachers before and after professional development that was designed to support them to understand and make incremental instructional shifts aligned with the NGSS. Findings indicate that teachers’ mental models shifted in two promising ways. First, teachers recognized that their roles and their students’ roles would need to change, and second, the doing of science looks and sounds different than what was traditionally done in their classrooms. However, findings also suggest that teachers struggled to reconcile new ideas from the PD with their previous mental models of their classroom practice. These findings are significant because they indicate, teachers may have more fully-formed mental models for what science teaching and learning looks and sounds like when it is focused on what most would traditionally think of as classroom science doing (e.g., “doing labs”), or when it includes traditional knowledge dissemination structures (e.g., lectures). This has important implications for science teacher educators and researchers, which will be discussed. © 2020, © 2020 Association for Science Teacher Education.
Keywords: NGSS; Science teacher education; dept.cur; mental models; peer-reviewed; professional development; teacher drawings; teacher practical knowledge